Syringe-mediated syndemics. - Bulled, Nicola; Singer, Merrill (AIDS and behavior, 2011)
One consequence of the global HIV/AIDS pandemic has been the emergence of a broad awareness of the potential role of syringes in the transmission of infectious diseases. In addition to HIV/AIDS, the use of unsterile syringes by multiple persons has been linked to the spread of Hepatitis B, Hepatitis C, Leishmaniasis, malaria and various other infections. The purpose of this paper is to extend awareness of the grave risks of multiperson syringe use by examining the role of this behavior in the development of infectious disease syndemics. The term syndemics refers to the clustering, often due to noxious social conditions, of two or more diseases in a population resulting in adverse disease synergies that impact human life and well-being. The contemporary appearance and spread of identified syringe-mediated syndemics, and the potential for the emergence of future syringe-mediated syndemics, both of which are reviewed in this paper, underline the importance of public health measures designed to limit syringe-related disease transmission.
Keywords: Blood-Borne Pathogens; Communicable Diseases; Cross Infection; Disease Transmission, Infectious; Health Knowledge, Attitudes, Practice; Humans; Needle Sharing; Syringes